Respuesta :
Since g(x) varies with x, therefore:
g(x) = k/x where k is a constant.
So, first we need to get k. We are given that g(x) = 0.2 when x = 0.1
Substitute with these values to get k as follows:
g(x) = k/x
0.2 = k/0.1
k = 0.2*0.1 = 0.02
Now, the equation became:
g(x) = 0.02 / x
We need to get the g(x) when x = 1.6
Therefore, we will substitute with x in the equation and calculate the corresponding g as follows:
g(x) = 0.02 / 1.6
g(x) = 0.0125
g(x) = k/x where k is a constant.
So, first we need to get k. We are given that g(x) = 0.2 when x = 0.1
Substitute with these values to get k as follows:
g(x) = k/x
0.2 = k/0.1
k = 0.2*0.1 = 0.02
Now, the equation became:
g(x) = 0.02 / x
We need to get the g(x) when x = 1.6
Therefore, we will substitute with x in the equation and calculate the corresponding g as follows:
g(x) = 0.02 / 1.6
g(x) = 0.0125
0.0125 "Varies Inversely" means that when one of the items is multiplied by a constant, the other item is divided by the same constant. Or in mathematical notation. xy = k So let's calculate k. xg(x) = k 0.1 * 0.2 = k 0.02 = k
Therefore
g(x) = 0.02/x
Let's plug in the value 1.6:
g(1.6) = 0.02/1.6
g(1.6) = 0.0125
So our answer is 0.0125
Therefore
g(x) = 0.02/x
Let's plug in the value 1.6:
g(1.6) = 0.02/1.6
g(1.6) = 0.0125
So our answer is 0.0125